A Review of “Access to Care” Issues in Aortic Stenosis Patients: A Negative Report Card - Adam M. Reisman, MD; Sammy Elmariah, MD, MPH (Structural Heart)
The identification and management of patients with aortic stenosis exist along a continuum that includes healthy living, latent progression, diagnosis, treatment, and posttreatment recovery. Barriers to the provision of appropriate care for these patients can occur at any stage along this continuum. Despite the presence of diagnostic echocardiograms, many patients with aortic stenosis are never clinically recognized, and the rate of mismanagement worsens among underrepresented minority groups and women. Regarding the treatment of clinically recognized aortic stenosis, only about half of patients with symptomatic severe aortic stenosis actually undergo aortic valve replacement within 2 ​years of diagnosis. Treatment rates are even lower among patients with symptomatic low-gradient severe aortic stenosis. Although several strategies have been raised by experts within the field to help and improve the diagnosis and treatment of patients with aortic valve disease, timely referral to a heart valve team specialist whenever aortic valve replacement is being considered likely remains the most pertinent intervention. Connecting these patients with fully informed aortic valve disease experts helps facilitate shared decision-making discussions, thus ensuring that patients have the opportunity to learn about and potentially receive the lifesaving interventions available to them.